Louise Lawler - Receptions - Marcoci, Roxana 19XX- (The Museum of Modern Art, 2017)
"Published in conjunction with the exhibition 'Louise Lawler: WHY PICTURES NOW', at The Museum of Modern Art, this volume charts the creative practice of one of the most influential artists working in the fields of picture-making and institutional critique. For the past 40 years, Louise Lawler has raised questions about art-about the circumstances that produce it, its circulation and the societal frameworks in which it appears. Many of the ideas that arise out of her work relate to theories of reception, the belief that the meaning of an artwork shifts and morphs depending on who looks at it and where it is seen. As the title of this publication suggests, many kinds of reception are possible."- Published in conjunction with the exhibition 'Louise Lawler: WHY PICTURES NOW', at The Museum of Modern Art, New York, April 30-July 30, 2017. -
Includes bibliographical references (pages 238-246) and index
Keywords: Lawler, Louise -- 1947-; Geschichte 1974-2016; Fotografie; Lawler, Louise / Exhibitions; Photography of art / Exhibitions; Photography, Artistic / Exhibitions; Ausstellungskatalog; Ausstellungskatalog -- Museum of Modern Art -- 30.04.2017-30.07.2017 -- New York, NY; Bildband